PREVALENCE OF ANTIBODIES AGAINST AVIAN PARAMYXOVIRUS TYPE 1 IN BACKYARD TURKEYS IN FOUR PROVINCES OF LIMA, PERU - Santa Cruz J., Franklin (2013)
The objective of the study was to determine the prevalence of antibodies against avian Paramyxovirus type 1 (APMV-1) in backyard turkeys (n=388) in four provinces of Lima, Peru (Lima, Huaral, Huaura, and Barranca). Blood samples were collected from August to December 2008 and analyzed by hemagglutination inhibition test. The resulting seroprevalence was 3.9% as 15/388 turkeys showed antibody titers consistent with a viral challenge of APMV-1. The highest frequency of positive samples (10/15) was observed in the province of Lima, whereas none sample was positive in the Barranca province. It is concluded that backyard turkeys in three provinces of Lima were exposed to some strains of PMVA-l, constituting a reservoir of virus.